Public Service Innovation In The Digital Era (Study On The Implementation Of E-Government In Government Durian Demang Village, Karang Tinggi District, Central Bengkulu Regency) - Lesmana, Arif; Soleh, Ahmad; Kresnawati, Kresnawati (Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to determine the innovation of E-government-based public services in Durian Demang Village government, Karang Tinggi Sub-district, Central Bengkulu Regency. This research uses a qualitative method with a case study research type to obtain an in-depth understanding of the implementation of E-government at the village level. The results showed that Durian Demang Village has made a significant digital transformation in three main aspects, namely administrative processes, workflows, and operational procedures. The implementation of SIAK version 7.0, digital biometric verification system, as well as queue and service automation has improved service efficiency and accuracy. The development of e-government platform based on Durian Demang Digital application has also improved the accessibility and transparency of public services. Village governance and conceptual innovation also support increased public participation and collaboration with the private sector in service development.